Two-phase flow in submersible electric pumps: a bibliometric analysis - Oliveira, Fernando Cyrilo de; Reis, Marcelo Cardoso dos; Rodrigo (Brazilian Journal of Production Engineering, 2021)
The technological challenges in oil and gas production have increased considerably in recent years due to the pursuit of safety, cost reduction and optimization of production, as indicated by the large number of studies on the guarantee of disposal. A major concern is related to the multiphase flow with heat exchange in submarine equipment, where different flow patterns can occur. The present work carried out a bibliometric research in the base SCOPUS®, analyzing the volume of publications in the area and the most relevant contributions about the biphasic flow in submersible horizontal pumps. The research initially looked for articles that contained the words "horizontal pump gas liquid ESP (Eletrical Submersible Pump)", after a refinement, were chosen the 5 most recent articles in the database used.
Keywords: ESP; Submersible electric pumps; Biphasic; Horizontal flow